Willie the Wildcat holding the book "Ready Player One" - Kansas State University, K-State First (Kansas State University. K-State First., 2013)
Photo of Kansas State University's mascot, Willie the Wildcat, at the 2013 June Orientation and Enrollment for first-year students holding the selected 2013 Kansas State common book, "Ready Player One" by Ernest Cline.
Keywords: Ready Player One; Mascot; Orientation; Promotional materials